2019
DOI: 10.1016/j.mbplus.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

CCL2/MCP-1 signaling drives extracellular matrix turnover by diverse macrophage subsets

Abstract: Macrophage plasticity, cellular origin, and phenotypic heterogeneity are perpetual challenges for studies addressing the biology of this pivotal immune cell in development, homeostasis, and tissue remodeling/repair. Consequently, a myriad of macrophage subtypes has been described in these contexts. To facilitate the identification of functional macrophage subtypes in vivo , here we used a flow cytometry-based assay that allows for detailed phenotyping of macrophages engaged in extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…However, polarization of M2-to-M1-like macrophages was detected in the spleen after celecoxib administration. In line with a previous study ( Jürgensen et al., 2019 ), emerging data suggested that M1-like (F4/80 + Ly6c + ) macrophages have a higher capacity of collagen and fibrin uptake for tissue repair after injury compared with M2-like macrophages and that no significant reduction of M2-like macrophages can be observed. Taken together, our data demonstrated that celecoxib can inhibit cardiac hypertrophy and fibrosis in non-regenerative mice by regulating M1-like macrophage infiltration.…”
Section: Discussionsupporting
confidence: 91%
“…However, polarization of M2-to-M1-like macrophages was detected in the spleen after celecoxib administration. In line with a previous study ( Jürgensen et al., 2019 ), emerging data suggested that M1-like (F4/80 + Ly6c + ) macrophages have a higher capacity of collagen and fibrin uptake for tissue repair after injury compared with M2-like macrophages and that no significant reduction of M2-like macrophages can be observed. Taken together, our data demonstrated that celecoxib can inhibit cardiac hypertrophy and fibrosis in non-regenerative mice by regulating M1-like macrophage infiltration.…”
Section: Discussionsupporting
confidence: 91%
“…When investigating BMDMs (M-CSF derived) and BMDCs (GM-CSF derived) generated from CCL2 knockout and CCR2 knockout mice, Chen et al found reduced phagocytosis (of Escherichia coli) and endocytosis (of dextran) compared to BMDMs of wild-type mice (108). Furthermore, the CCL2/CCR2 axis seems to be essential for macrophage-mediated endocytosis of collagen and fibrin (111,171). This ECM turnover is critical during tissue remodeling and repair (197).…”
Section: Increase Of Phagocytosis Efferocytosis and Endocytosis Of mentioning
confidence: 99%
“…Moreover, TGFβ in conjunction with tenascin-C are associated with an epithelial to mesenchymal transition (EMT) of breast cancer cells ( 82 ), and stimulation of macrophages by TGFβ force them to produce type VI collagen ( 83 ). Finally, although not in models of tumorigenesis, but during experimental dermal remodeling, CCR2 expressing macrophages directly degraded collagen and fibrins, and the addition of GM-CSF selectively enhanced their collagen endocytosis capacities, likely via the proliferation-inducing capacities of this cytokine ( 84 ). These data suggest an involvement of the CCL2/CCR2 axis in matrix remodeling and tissue repair mechanisms, in favor of a positive reinforcement loop between the ECM and macrophages; it is for example known that collagen degradation products can play a chemotactic role towards macrophages, which may contribute to their recruitment to the tumor site ( 85 ).…”
Section: Introductionmentioning
confidence: 99%